Allergic asthma and rhinitis comorbidity - Zvezdin, Biljana S (Vojnosanitetski pregled, 2015)
Based on available evidence, allergic respiratory diseases-asthma and rhinitis, are duly considered the 21st century epidemic and modern age diseases. The World Health Organization estimates there are 300 million asthmatics in the world, and 500 million people with rhnitis symptoms. The number of patients may be expected to further increase in the future, particularly among children and adolescents in both high-developed and undeveloped countries. Very often, asthma and rhinitis coexist in the same patient. Numerous contemporary studies, guided by the concept „one airway-one diseases“, have revealed the epidemiological, pathophysiological and clinical correlation of asthma and rhinitis. Both diseases are very often undiagnosed, especially when they simultaneously coexist in the same patient. The coexistence of rhinitis and asthma is not a new discovery. The connection of the upper and lower airways had been empirically noticed long ago. As early as in the2nd century, Galen advised his patients to „clean the nose in order to protect the lungs“. It is therefore surprising that it took centuries to confirm the concurrence of asthma and rhinitis by the strength of arguments and emphasize its importance. The concept of „a concurrent airway disorder” has important implications for both diseases (asthma and rhinitis), especially in diagnostic and therapeutic terms. Unidentified and untreated rhinitis in asthmatic patients represents a unique problem, making the control of asthma more difficult and significantly impairing the patients’ quality of life. The diagnosis and treatment of rhinitis is obligatory and should be included in the treatment of asthmatics. The untreated rhinitis accounts for frequent exacerbations of asthma, its difficult control and treatment, and bad prognosis. As both diseases are the chronic inflammatory ones, they require a long and continuous treatment. The latest guidelines for the treatment of concurrent asthma and rhinitis recommend the combined and gradual treatmernt strategy and approach. The adequate diagnostic management and combined treatment enable the affected patients to live a good quality life and perform their every-day personal, social and professional activities. This paper reviews the available evidence and reported results of allergic asthna-rhinitis correlation studies carried out in our country, establishing the important fact that a comorbid rhinitis has a clinically strong impact on asthma.